Синтез систем активного экранирования магнитного поля воздушных линий электропередачи на основе многокритериальной оптимизации - Кузнецов, Борис Иванович; Никитина, Татьяна Борисовна; Волошко, Александр Валерьевич; Бовдуй, Игорь Валентинович; Виниченко, Елена Владимировна; Кобылянский, Борис Борисович (НТУ "ХПИ", 2016)
Проведен синтез систем активного экранирования техногенного магнитного поля, создаваемого различными воздушными линиями электропередачи внутри заданной области пространства, с помощью управляемых источников магнитного поля. Синтез сводится к решению задачи многокритериального нелинейного программирования c ограничениями, в которой вычисления целевых функций и ограничений выполняются на основании закона Био - Савара - Лапласа. Задача решается методом стохастической мультиагентной оптимизации мультироем частиц, что позволяет существенно сократить время решения. Приведены результаты синтеза систем активного экранирования для различных типов ЛЭП и с различным количеством управляемых обмоток. Показана возможность существенного снижения уровня индукции исходного магнитного поля внутри заданной области пространства.

Purpose. The synthesis of the active shielding systems by technogenic magnetic field generated by the different types of high voltage power lines in a given region of space using various cables of controlled magnetic field sources. Methodology. The initial parameters for the synthesis of active shielding system parameters are the location of the high voltage power lines with respect to the protected transmission line space, geometry and number of cables, operating currents, as well as the size of the protected space and normative value magnetic field induction, which should be achieved as a result of shielding. The objective of the synthesis of the active shielding system is to determine their number, configuration, spatial arrangement, wiring diagrams and compensation cables currents, setting algorithm of the control systems as well as the resulting value of the induction magnetic field at the points of the protected space. Synthesis of active shielding system is reduced to the problem of multiobjective nonlinear programming with constraints in which calculation of the objective functions and constraints are carried out on the basis of Biot – Savart – Laplace law. The problem is solved by a stochastic multi-agent optimization of multiswarm of particles which can significantly reduce the time to solve it. Results. Active screening system synthesis results for the various types of transmission lines and with different amounts of controlled cables is given. The possibility of a significant reduction in the level of induction of the magnetic field source within a given region of space. Originality. For the first time carried out the synthesis of the active shielding systems, by magnetic field generated by the different types of high voltage power lines within a given region of space controlled by a magnetic field sources with different amounts of controlled cables. Practical value, Practical recommendations on reasonable choice of the number and spatial arrangement of compensating cables of active shielding systems for different types of high voltage power lines in order to ensure the effectiveness of a given shielding of the magnetic field high voltage power lines.
Synthesis of an active shielding system of the magnetic field of power lines based on multiobjective optimization
Keywords: воздушные линии электропередачи; магнитное поле; система активного экранирования; многокритериальный синтез; стохастическая мультиагентная оптимизация; мультирой частиц; power lines; power frequency magnetic field; active shielding system; multiobjective synthesis; stochastic multi-agent optimization; particle multiswarm